A comparative analysis of building materials for sustainable construction with emphasis on CO 2 reduction. (11th July 2012) - Shams, Shahriar; Mahmud, Kashif; Al-Amin, Md.
Building contributes almost 40% of CO2 emissions and is a major contributor to the green house gas (GHG) emissions. Different types of construction materials possess a wide variation of embodied energy and emit CO2 at different magnitudes during its life cycle. Selection of appropriate construction materials can considerably cut down CO2 emissions and make our buildings more sustainable and energy efficient. The study is an attempt to address the issues of sustainable construction and how its selection of construction materials can reduce CO2 emissions and play an important role in reducing the impact of climate change directly or indirectly. A case study for a typical house having 90 sq. m. of plan area was analysed to see the variation of CO2 emission based on altering the types of construction materials to be used. It has been observed from the case study that construction materials like aluminium and steel should be less encouraged due to their higher CO2 emission rate as compared to glass and timber.